A case study of human wildlife conflict at Bakhira Lake - Abhishek, Kumar Singh; Prateek, Shahi (I-Manager's Journal on Civil Engineering, 2025)
The Bakhira Lake is the largest natural floodplain wetland in India, in Sant Kabir Nagar, Uttar Pradesh. It supports a rich diversity of flora and fauna; however, human activity such as farming, fishing, hunting, tourism, and industrialization harmed the ecological balance, leading to loss of habitat & biodiversity. According to a report by Wetland International South Asia, over 70% of wetland boundaries are affected by agricultural expansion, and illegal hunting has led to a 20% decline in certain migratory bird populations over the decade. Water pollution, particularly from industrial discharge, has increased biochemical oxygen demand (BOD) levels by 30% in the last 5 years, significantly affecting aquatic biodiversity. Climate change further increases this challenge by changing precipitation patterns and high temperatures and influencing the migration and breeding behavior of various species. This paper examines how these factors affect the biodiversity of the lake, particularly looking at the bird and fish populations along with environmental aspects of habitat disturbance in migration and water quality indicators such as BOD, total dissolved solids (TDS), and hardness. Additionally, the study addresses conservation strategies aimed at reducing these conflicts between humans and wildlife. The Bakhira Lake is the largest natural floodplain wetland in India, in Sant Kabir Nagar, Uttar Pradesh, covering 2,894 hectares, and serves as an essential habitat for resident and migratory birds. This paper seeks to examine the human-wildlife conflict at Bakhira Lake, pinpoint its causes, and propose effective conservation strategies.